Feeling stuck and feeling bad: Career plateaus, negative emotions, and counterproductive work behaviors - Ng, Kara; Yang, Wei‐Ning (Human resource management journal, 2024)
Career plateauing has been described as a subjective state that is emotionally unpleasant and associated with unethical work behaviors, yet there is little theoretical explanation or robust evidence to support such claims. This study contributes a theoretical framework for the relationships between career plateauing, emotions, and counterproductive work behaviors (CWB). Building on the stressor‐emotion model of CWB, we propose that employees who perceive themselves as experiencing plateau are likely to commit CWB when they experience negative emotions. We also predict that the strength of this process depends on individuals' emotion regulation ability. Through regression analysis of data from 193 UK‐based employees across three time points, our study finds that both hierarchical and job content plateauing are associated with negative emotions and indirectly related to CWB via negative emotions; neither plateau type is directly related to CWB. Additionally, lower emotion regulation ability strengthens the relationship between job content plateauing and negative emotions, leading to more CWB. This study offers a novel theoretical explanation of how plateauing affects employees' emotions and deviant behaviors. It also provides important practical guidance for managers by showing that plateaued employees are not inherently problematic to the organization. By proactively understanding and managing plateaued individuals' feelings, managers can more likely prevent negative emotions from triggering deviant behaviors.